Processing the overlay of geometry segments in solving hydrophysics problems by the finite difference method - Litvinov Vladimir; Gracheva Natalya; Rudenko Nelli (E3S Web of Conferences, 2022)
The article deals with issues related to increasing the efficiency of working with data on the geometry of the computational domain when solving hydrophysics problems using the finite difference method. The model problem is a system of equations of the pollutant distribution, including the oil and its refined products, in the computational domain – Azov Sea. To describe the computational domain, a model of a two-dimensional computational grid is used, which is used in the implementation of numerical calculations. Class diagrams are presented for describing the geometry of the object under study, as well as its constituent segments. In order to improve the performance of calculations, an algorithm for combining geometry segments was developed, in which the original algorithm was divided into separate fragments by introducing a number of conditional structures. As a result of experimental data processing, regression equations were obtained that describe the dependence of the algorithm execution time on the number of joins. The developed algorithm and class library make it possible to work with the description of the geometry of the object under study as a set of parameterized primitives and educe the time spent on the formation of the description of the computational domain by up to 27%.